Prevalence of enteroparasites in beach sand in the municipality of São Luís-MA (Research, Society and Development, 2020)
This study aimed to investigate the contamination by enteroparasites in beach sand in the municipality of São Luís-MA. To this end, a descriptive and exploratory study was carried out with the collection of sand samples from beaches and analysis in the laboratory. Qualitative methods were used with the spontaneous sedimentation technique Hoffman, Pons and Janer, Lutz. The samples were analyzed for the presence of helminth eggs and protozoan cysts. 70 sand samples were analyzed on 04 beaches at 14 collection points. The contamination of beach sands in the municipality of São Luís-MA was confirmed by the detection of parasitic structures. The beaches of São Luís are considered unsuitable for bathing, in addition to the contamination of sea water by bacteria as determined by public agencies in the first half of 2017 and according to the data of this research. The importance of monitoring beach sand and possible actions to improve sanitary conditions in São Luís-MA were also identified.